2022
DOI: 10.1007/s43452-022-00424-6
|View full text |Cite
|
Sign up to set email alerts
|

Real fracture toughness of FRC and FGC: size and boundary effects

Abstract: The present dilemma is how to simulate the real crack in full depth (FD) fiber-reinforced concrete (FRC), FD FRC, to get the actual fracture toughness of such fibrous composites, i.e., through-thickness pre-cracks are inappropriate for such materials. To overcome this dilemma, a new technique was adopted to create a pre-matrix crack (MC) without cutting the fibers bridging the two surfaces of the pre-crack. The main objective of the present work is to study the size and boundary effects on the real fracture to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The d max /NMAS were calculated, and the results are given in Table 11. The ratios of d max /NMAS in the current study ranged between 1 and 2 in MC specimens, near the ratios found by Elakhras et al [36][37][38] for mode I, which were greater than unity.…”
Section: Real Fracture Toughness Of MC Frcsupporting
confidence: 80%
See 3 more Smart Citations
“…The d max /NMAS were calculated, and the results are given in Table 11. The ratios of d max /NMAS in the current study ranged between 1 and 2 in MC specimens, near the ratios found by Elakhras et al [36][37][38] for mode I, which were greater than unity.…”
Section: Real Fracture Toughness Of MC Frcsupporting
confidence: 80%
“…Unfortunately, such previous work was not only a waste of time and effort but also led the scientific research compass in this field in the wrong direction for solving such problems. The first attempt in the right direction for predicting the fracture toughness of fibrous composite materials was made by Salam and colleagues [34,[36][37][38][39]. Sallam and co-workers [36,39] successfully correlated the mode I fracture toughness of FRC using MC specimens, i.e., correlating a vectorial problem with a crack path independent of the initial crack length by scalar parameters such as Griffith's energy release rate..…”
Section: Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Many experimental studies have shown that the fracture parameters obtained from small‐ and medium‐sized specimens cast in the laboratory have significant size effects 11–16 . In other research findings, the fracture parameters of different materials were mainly studied to determine these parameters without size effects 17–24 .…”
Section: Introductionmentioning
confidence: 99%